The Commodification of People with Mental Disorders on Pratiwi Noviyanthi's YouTube Channel - Lativa Nur Santy; Qadzafi, Syafawi Ahmad (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2024)
People with mental disorders have their rights as part of Indonesian citizens. The existence of social experimental content related to people with mental disorders makes them vulnerable to becoming objects of commodification. This study aims to determine the form of commodification practices of people with mental disorders on Pratiwi Noviyanthi's YouTube channel. Using Roland Barthes' semiotic analysis, the researcher wants to see the meaning of denotation, connotation, and myth on Pratiwi Noviyanthi's YouTube channel in the case of an old woman with long nails in Surabaya. This research found 7 scenes depicting social exploitation and dramatization of scenes that play a role in the practice of commodification of people with mental disorders on Pratiwi Noviyanthi's YouTube channel, in the case of an old woman with long nails in Surabaya. The commodification of people with mental disorders is carried out through social content that ignores their rights to protection from exploitation and discrimination. This content is presented with various editing approaches and techniques, such as adding background music, color changes, and visual effects to dramatize the scene. This aims to attract viewers' attention to Pratiwi Noviyanthi's YouTube channel. Viewer interaction is converted into economic profit through advertisements embedded in Pratiwi Noviyanthi's content about people with mental disorders.